2020
DOI: 10.1002/app.49259
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ethylene glycol)‐interpenetrated genipin‐crosslinked chitosan hydrogels: Structure, pH responsiveness, gelation kinetics, and rheology

Abstract: In the development of pH‐responsive chitosan‐based hydrogels, achieving reproducible porosity and swelling behavior is essential for the design of hydrogel networks. Herein, we enhance the level of control in hydrogel microarchitecture by incorporating poly(ethylene glycol) (PEG) into the chitosan–genipin matrix. Hydrogels, varied in composition, were synthesized under mild conditions (37°C, 1 atm, 24 hr), yielding microporous structures with a pore diameter ranging from 11 to 57 μm and an average cross‐sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 71 publications
1
36
0
Order By: Relevance
“…This suggests existence of an optimal range of genipin concentration beyond which PEG addition may lead to a reduced number of effective crosslinking between chitosan and genipin. These findings support the results from our previous study, which revealed the link between PEG content and the sudden change in hydrogels' swelling capacity, gelation kinetics and mechanical strengths 29 . Methodology used to follow the degradation of theses gels in vitro is an innovative and yet simple approach to deploy the intrinsic fluorescence of the chitosan‐genipin links for tracking the biodegradation in vitro, and possibly in vivo too.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…This suggests existence of an optimal range of genipin concentration beyond which PEG addition may lead to a reduced number of effective crosslinking between chitosan and genipin. These findings support the results from our previous study, which revealed the link between PEG content and the sudden change in hydrogels' swelling capacity, gelation kinetics and mechanical strengths 29 . Methodology used to follow the degradation of theses gels in vitro is an innovative and yet simple approach to deploy the intrinsic fluorescence of the chitosan‐genipin links for tracking the biodegradation in vitro, and possibly in vivo too.…”
Section: Discussionsupporting
confidence: 89%
“…Our microscopic images and viability assay show that hydrogels with higher genipin content (3.1 or 4.4 m m ) present better cytocompatibility to fibroblasts, in contrast to the counterparts with 1.7 m m genipin (Figure 1). Our previous study has evaluated the relation between genipin content and elastic modulus using small deformation rheology measurements 29 . We found that increasing genipin content from 3.1 to 6.3 m m significantly increased elastic modulus (from ~ 445 to ~ 1100 Pa) and shortened the linear viscoelastic region by 50%, suggesting a positive correlation between genipin content and hydrogels' rigidity.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations